Students of State Elementary School 2 Cintaratu Received Health Education on Dengue Fever Prevention (DHF) as an Indicator of a Clean Lifestyle (PHBS) - Dadang Purnama; Iwan Shalahudin; Udin Rosidin; Nina Sumarni; Witdiawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
DHF can occur at any time of year and affect people of all ages. This disease is linked to environmental factors and community behavior. Several circumstances can lead to the establishment of DHF in the educational setting. There are two types of factors: internal and external. Internal factors of transmission may include a person's immunity. The conditions of various mosquito breeding places, such as water reservoirs, can be used to determine what causes a person to suffer from DHF since these factors allow mosquitos to thrive and breed. This is because the water reservoir at SDN 2 Cintaratu appears moist, lacks sunlight, is not cleaned, and is not closed. The purpose is to develop understanding and modify the behavior of public elementary school pupils 2 Cintaratu in order to avoid risk factors for DHF. Lecture, question and answer, discussion, and demonstration are the methods employed. The whole audience consisted of 48 students aged 9 to 12. In this pre-test question, there are 5 multiple-choice questions with the number of scores on each question is 20 points. This question leads to the student's cognitive dominance to determine the level of students' knowledge about dengue hemorrhagic fever before being provided the material. Based on the pretest and posttest scores, the average number of prestests was 58%, with 15 students scoring below average and 33 scoring above average. The average number of posttests was 72%, with 11 students scoring less than the norm, and 37 students scoring more. Conclusion: In achieving the objectives of health promotion carried out, there are four indicators that will be achieved for students from eight PHBS indicators in the school environment, namely, washing hands with clean running water and soap, using clean and healthy toilets, eradicating mosquito larvae, and managing and disposing of waste in its place